Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2016/1541823
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Implications for Extracellular Matrix‐Based Technologies in Vascularized Composite Allotransplantation

Abstract: Despite recent progress in vascularized composite allotransplantation (VCA), limitations including complex, high dose immunosuppression regimens, lifelong risk of toxicity from immunosuppressants, acute and most critically chronic graft rejection, and suboptimal nerve regeneration remain particularly challenging obstacles restricting clinical progress. When properly configured, customized, and implemented, biomaterials derived from the extracellular matrix (ECM) retain bioactive molecules and immunomodulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 169 publications
(183 reference statements)
0
25
0
Order By: Relevance
“…Sulfated GAGs include heparin sulfate, chondroitin sulfate, and keratin sulfate whereas non-sulfated GAGs include hyaluronic acid ( 4 , 57 ). GAGs are involved in cell proliferation, differentiation, growth, and adhesion along with cytokine and growth factor binding ( 4 , 46 ). For recellularization, retention of GAGs could be advantageous for retaining the tissue architecture as well as mechanical properties of a decellularized graft.…”
Section: Extracellular Matrix Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfated GAGs include heparin sulfate, chondroitin sulfate, and keratin sulfate whereas non-sulfated GAGs include hyaluronic acid ( 4 , 57 ). GAGs are involved in cell proliferation, differentiation, growth, and adhesion along with cytokine and growth factor binding ( 4 , 46 ). For recellularization, retention of GAGs could be advantageous for retaining the tissue architecture as well as mechanical properties of a decellularized graft.…”
Section: Extracellular Matrix Propertiesmentioning
confidence: 99%
“…Tissue engineered scaffolds obtained through decellularization and recellularization are an alternative option to circumvent these limitations. Decellularization allows the removal of cellular and nuclear content while preserving the tissue extracellular matrix (ECM) architecture, resulting in an ECM scaffolds with retained tissue-specific composition and structural integrity ( 4 ). The methods for decellularization, process parameters, and evaluation of decellularized scaffolds has been evaluated in solid organs and individual tissues ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, previous studies have shown that ECM materials are tissue-specific and possessed the different structures and biochemical components, which eventually promotes the viability and function of seeded cells better than simple type I collagen or tumor-derived matrigel. [38][39][40] Previous studies have demonstrated that the dose-response curve of PRP is not linear. High concentration of PRP may even have an inhibitory effect on cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mass spectrometric analysis revealed that PEM solution digested by pepsin contains many protein peptides, such as collagen, laminin, elastin, proteoglycan, and tissue‐specific protein precursors (Table 3). Also, previous studies have shown that ECM materials are tissue‐specific and possessed the different structures and biochemical components, which eventually promotes the viability and function of seeded cells better than simple type I collagen or tumor‐derived matrigel 38‐40 …”
Section: Discussionmentioning
confidence: 99%
“…Wong et al make the case for such progress in reconstructive surgery through applications of tissue engineering and regenerative medicine facilitated by nanotechnology [8]. They predict there will be a big impact in the area of wound healing (e.g., biodegradable drug eluting dressings, microbiological or oxygen sensors), nerve regeneration (e.g., molecular imaging), soft tissue or bone reconstruction (e.g., prefabricated vascularized conduits or bioscaffolds for stem cell or fat graft delivery, smart nanocoatings for breast implants, 3D printed biointegrable nanocomposites for bone regeneration), ex vivo engineered tissue interfaces and vascularized composite constructs, and targeted nanomedicine strategies for multipronged applications (e.g., antirejection, antifibrotic or antineoplastic therapies to improve outcomes of conventional reconstructive or VCA procedures) [9].…”
mentioning
confidence: 99%